REAL EUKARYOTES AND PRECIPITATES FIRST FOUND IN THE MIDDLE RIPHEAN STRATOTYPE, SOUTHERN URALS - Sergeev V.N.; Seong-Joo L. (My University, 2006)
New investigations considerably extended taxonomic list of microbiotas from cherts of the Kataskin and Revet subformations of the Avzyan Formation in the Yurmata Group, the Middle Riphean stratotype in southern Urals. It is recognized in distinction from previous works that found remains of eukaryotic unicellular organisms represent a considerable percentage of fossil microbial population buried in the Kataskin Subformation. In addition to cyanobacteria known before, cherts of the subformation yielded fossil microorganisms representing eukaryotic phytoplankton. These remains described formerly as organic-walled microfossils from siliciclastic sediments of the Zigazino-Komarovo and Avzyan formations had not been known from cherty-carbonate strata of the Middle Riphean. The discovery is consistent with recent data on microfossils of complex morphology present in silicified microbiotas, which has been regarded as prokaryotic exclusively. Layered inorganic precipitates found for the first time in the Kataskin Subformation are widespread in pre-Upper Riphean successions and disappear near the Middle-Upper Riphean boundary. Besides, silicified cyanobacterial remains described formerly from the Avzyan Formation are revised, and their formal composition is corrected in accord with the present-day classification of fossil blue-green algae. The correction results and new microfossils found elucidate microphytological characterization of the Middle Riphean that is important for biostratigraphic correlation of Proterozoic deposits and helps to solve some problems of taxonomy of Precambrian microfossils. The assemblage of microfossils from the Avzyan Formation offers a unique opportunity to understand a transitional moment in history of Proterozoic microorganisms, when entophysalidacean and stalked cyanobacteria developed jointly parallel to expansion of eukaryotic unicellular algae into prokaryotic ecosystems. The work includes description of 10 microfossil species attributed to 7 genera. © MAIK "Nauka/Interperiodica" 2006.
Keywords: CYANOBACTERIA; EUKARYOTIC PHYTOPLANKTON; MICROFOSSILS; MIDDLE RIPHEAN; PROKARYOTES; RIPHEAN TYPE SUCCESSION; SOUTHERN URALS; Докембрий::Протерозой::Рифей; Precambrian::Proterozoic::Riphean